Epidemiology of peste des petits ruminants virus in West Africa: Is lineage IV replacing lineage II in Burkina Faso? - Biguezoton, A.S.; Ilboudo, Guy S.; Wieland, Barbara; Sawadogo, R.; Dah, F.; Zoungrana, A.; Dione, Michel M. (International Livestock Research Institute, 2022)
Objective This study aimed at investigating the lineages of peste des petits ruminants virus (PPRv) currently circulating in Burkina Faso.